DExIMA: Design Explorer for In-Memory Architectures - Andrea Coluccio; Alessio Naclerio; Marco Vacca; Giovanna Turvani; Mariagrazia Graziano; Maurizio Zamboni (IEEE Access)
In recent years, Computer-Aided Design (CAD) software have become indispensable tools for designing, testing, and synthesizing logic circuits. Commercial software provided by companies like Synopsys, Cadence, or Mentor dominate the Electronic Design Automation (EDA) field. Nevertheless, several Open Source tools are also available, and some of them aim at assisting the designer in emerging Beyond-von-Neumann computing paradigms, such as Logic-in-Memory (LiM). LiM is a promising architectural and technological solution to the von Neumann Bottleneck, i.e. the performance gap between the CPU and the memory in classical CPU-Memory structures. In literature, various approaches to the LiM paradigm have been proposed. This paper introduces the Design Explorer for In-Memory Architectures (DExIMA) tool, which has the ambitious aim of providing a well-defined design flow strategy for the development, validation and performance estimation of a wide range of LiM architectures. Currently, DExIMA focuses on Coarse-grain Logic-in-Memory (CGLiM) architectures, which integrate memory and computation elements at a coarse-grain level. Nevertheless, DExIMA encompasses a flexible architectural model and a modular performance estimation engine that can be adapted to LiM implementations where memory and logic elements are more finely integrated. Hence, DExIMA is a versatile tool offering an environment for testing and comparing different LiM solutions, empowering designers to explore novel approaches in LiM architecture design.